Pengaruh Keteraturan Membaca dan Penghayatan Makna Ayat Al-Qur'an pada Kemampuan Berpikir Positif Narapidana - Aida Dakhliyah Sufriani; R.A Retno Kumolohadi (Universitas Islam Indonesia, 2009)
This study is aimed to examine the impact of reading on the regular basis and comprehending Al-Qur'an training to increase positive thinking ability. The hypothesis of this research is that there is, a positive correlation between the training and positive thinking ability. The prisoners who followed training had more positive thinking ability. There are twenty prisoner from Yogyakarta Penintentiary Class IIA that were involved in the research. Many aspects from Albrecht conception were used to make 50 items scale. Pre-post test control group design is the experimental design of this research. From quantitative analysis SPPS Program version 11,5 for windows, researcher obtain scores between two groups (p=0.0125; p < 0.05), therefore the hypothesis is accepted.Keywords : positive thinking, reading an the regular bases, meaning Qur'an